Potassium citrate and metabolic acidosis in children with epilepsy on the ketogenic diet: a prospective controlled study. (19th November 2019) - Bjurulf, Björn; Magnus, Per; Hallböök, Tove; Strømme, Petter
Abstract : Aim: To investigate if potassium citrate, a mild alkaline compound, can prevent metabolic acidosis in children with epilepsy treated with the ketogenic diet without reducing antiepileptic efficacy. Method: In this prospective controlled study, we investigated the frequency of initial uncompensated metabolic acidosis in 51 participants. There were 22 participants with and 29 without potassium citrate supplementation. The ketogenic diet was used as add‐on treatment to children with drug resistant epilepsy. We also estimated the proportion of participants with a greater than 50% seizure reduction after 7 months. Results: None of the 22 participants (15 males, seven females; median age 1y 7mo, interquartile range [IQR] 3y 3mo) with, and 10 of 29 (12 males, 17 females; median age 6y 1mo, IQR 4y 8mo) without potassium citrate developed metabolic acidosis (odds ratio=0.04, 95% CI 0.00–0.75 [ p <0.01]); median pH 7.32 vs 7.24; [ p <0.001]), and median bicarbonate 19.7mmol/L vs 14.0mmol/L ( p <0.001). The number of seizures was reduced by more than 50% in 9 of 22 with potassium citrate and 8 of 29 participants without potassium citrate, 7 months after introducing a ketogenic diet ( p =0.4). Interpretation: In the ketogenic diet, potassium citrate supplementation can prevent metabolic acidosis, without reducing antiepileptic efficacy. What this paper adds: Citrate supplementation prevents metabolic acidosis in children treated with a ketogenic diet. Efficacy of the ketogenic diet is not affected by supplementation with citrate. Citrate supplementation does not affect beta‐hydroxybuturate concentration. Potassium citrate reduces the time needed to reach an optimal ketogenic ratio. This article is commented on by Schoeler on page 8 of this issue. What this paper adds: Citrate supplementation prevents metabolic acidosis in children treated with a ketogenic diet. Efficacy of the ketogenic diet is not affected by supplementation with citrate. Citrate supplementation does not affect beta‐hydroxybuturate concentration. Potassium citrate reduces the time needed to reach an optimal ketogenic ratio.